Dietary Phospholipids Prepared From Scallop Internal Organs Attenuate the Serum and Liver Cholesterol Contents by Enhancing the Expression of Cholesterol Hydroxylase in the Liver of Mice - Sugimoto, Koki; Hosomi, Ryota; Yoshida, Munehiro; Fukunaga, Kenji (Frontiers in Nutrition, 2021)
In this study, we successfully prepared scallop oil (SCO), which contains high levels of phospholipids (PL) and eicosapentaenoic acid (EPA), from the internal organs of the Japanese giant scallop (Patinopecten yessoensis), one of the most important underutilized fishery resources in Japan. The intake of SCO lowers the serum and liver cholesterol contents in mice; however, whether the fatty acids (FA) composition or PL of SCO exhibits any cholesterol-lowering effect remains unknown. To elucidate whether the cholesterol-lowering function is due to FA composition or PL of SCO, and investigate the cholesterol-lowering mechanism by SCO, in the present study, mice were fed SCO’s PL fraction (SCO-PL), triglyceride (TG)-type oil with almost the same FA composition as SCO-PL, called SCO’s TG fraction (SCO-TG), soybean oil (SOY-TG), and soybean’s PL fraction (SOY-PL). Male C57BL/6J mice (five-week-old) were fed high-fat and cholesterol diets containing 3% (w/w) experimental oils (SOY-TG, SOY-PL, SCO-TG, and SCO-PL) for 28 d. The SCO-PL diet significantly decreased the serum and liver cholesterol contents compared with the SOY-TG diet, but the intake of SOY-PL and SCO-TG did not show this effect. This result indicated that the serum and liver cholesterol-lowering effect observed in the SCO intake group was due to the effect of SCO-PL. The cholesterol-lowering effect of SCO-PL was in part related to the promotion of liver cholesterol 7α-hydroxylase (CYP7A1) expression, which is the rate-limiting enzyme for bile acid synthesis. In contrast, the expression levels of the ileum farnesoid X receptor (Fxr) and fibroblast growth factor 15 (Fgf15), which inhibit the expression of liver CYP7A1, were significantly reduced in the SCO-PL group than the SOY-TG group. From these results, the increase in the liver CYP7A1 expression by dietary SCO-PL was in part through the reduction of the ileum Fxr/Fgf15 regulatory pathway. Therefore, this study showed that SCO-PL may be a health-promoting component as it lowers the serum and liver cholesterol contents by increasing the liver CYP7A1 expression, which is not seen in SOY-PL and SCO-TG.